Hydrodynamics and water quality assessment of lakes by termal behaviour and modelling. - Amorim, Laís Ferrer (2020)
This thesis is divided into five chapters, which explain the hydrodynamic and environmental modelling theoretical base, the hypotheses investigated in this work, the scientific contributions produced building the thesis and the suggestion to next researches.The context in which this research was built is described in the first chapter, along with the knowledge gaps and investigated questions. It presents the fundamental base, about lake hydrodynamic, water quality and mathematical modelling.The investigated hypotheses are described in chapters II and III. In the second one, the methods were applied in four different lakes to build a curve that describes the lake thermal stability, according to the atmospherical driving forces. Then, chapter III presents the quasi-3D model results in hydrodynamics, water quality, and bed material resuspension of two lakes. Chapter IV evaluates those two management tools in terms of reliability, quickness, types of results and complexity. Climate change simulations were performed in two lakes, aiming to demonstrate the use of those two tools.The final chapter brings the general discussions, the thesis main scientific contributions, and the directions to the next researches, along with the bibliography used in the work. The whole scheme of the thesis is demonstrated in Figure 1.